Summation of independent random values of the Ries method - Matsak , I. K. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Under moment restrictions on Х1 exact sufficient conditions are established on the growth of ап for the convergence almost surely of weighted Riesz means An-1 Σ1n ai Xi to MX1, where (Xn) is a sequence of independent identically distributed random variables, (аn) is a positive numerical sequence Аn = Σ1n ai.